Innovation and employment growth: Evidence from manufacturing firms in Africa - Ibrahim Mike Okumu; Edward Bbaale; Madina Mwagale Guloba (Journal of Innovation and Entrepreneurship, 2019)
This paper estimates the association between innovation and employment growth among manufacturing firms in Africa. The paper uses a cross-sectional World Bank Enterprise Survey dataset in which innovation is categorised as product innovation and process innovation. Results from the pooled ordinary least squares (OLS) estimation are more efficient compared to IV 2SLS. The pooled OLS results indicate that: (1) employment growth is positively associated with both process and product innovation, (2) a weak business environment especially intermittent electricity supply undermines the ability of innovation to induce employment growth and (3) relationship between innovation and employment growth is not conditioned on firm age although it is conditioned on firm size. Such findings suggest that employment growth in Africa could benefit from policies and programs that induce firms to embrace innovation. In addition, a strong business environment is necessary in complementing the potential of innovation to enhance employment growth in Africa.
Keywords: D2; J23; O31; O33; O55; 650; Employment; Product innovation; Process innovation; Africa